Anúncios de emprego para enfermeiros entre 1966 e 1985 em jornais paulistanos de grande circulação - Ramponi, Kenny Paolo [UNIFESP] (2017)
Objective: Analyze and describe the Nursing job offers and benefits announced on São Paulo’s general circulation newspapers between January of 1966 and Decem ber 31, 1985. Method: Historical documentary study made of quantitative analysis and serial research. The collected data include access to the newspapers archives of Folha de São Paulo and Estado de São Paulo; It was also extended to a physica l newspaper library. All the data were sent to a database divided into three groups: (1) Professional Requirements, consisting of seven sub-items, (2)Conditions, with 2 1 sub-items, and (3)Job Profile, having three sub-items. From the compilation, the data were divided into four periods to be analyzed. The Fisher test was applied in c onjunction with the trends verification, using the Cochran-Armitage test and the line ar association between requirements and benefits that was being offered. Results: A total of 614 ads were found in both newspapers, in which 319 of them were ads r ecruiting nurses and 292 were about nurses offering their services to the market. T hus, two forms of job filling were seen - Nurses recruitment and services offering b y nurses, concomitantly, also, was observed a continuous and increasingly dissemi nation of Job ad's on newspapers over the years, in both forms of fulfilling. There w as a variety of job benefits being offered, such as transportation, transportation vou cher’s, cafeteria, medical assistance, dental assistance, pharmaceutical assistance , academic incentives like scholarship and recreational clubs. Among the requirem ents made to become a nurse there was age, gender, work experience, Hourly rota tion and additional training. A progressive increase on requirements of membership in the class council since 1975 was perceived. The nurse job market was not very e xigent to professionals who intended to become a nurse at the time, which may be a consequence of a small number of nurses facing highs numbers of jobs to be fulf illed. In the recruitment ads there were different ways of naming Nurses, which hav e showed some variation during the processes of transformation of the profession. Among the nurses who offered their services to the market, a prevalence of valoriz ation of professional experience and length of service was noticed. Conclusion: T he Nurse Job market’ Study was limited to São Paulo's newspapers only, between 1966 and 1985, with two sources of research. Through a detailed analysis of worki ng conditions in the period studied, the profile of nurses who were recruited for the job market, as well as the nurses who offered themselves there, was characterized . It was also possible to identify what the market was requiring in order to fulfill the available jobs for nurses and the benefits that were being offered to them. Therefor e, it was possible to draw a panorama from the São Paulo's market situation for nu rses through the newspapers over the years of 1966 to 1985, concluding this perio d was favorable for the nurses.